THE INFLUENCE OF THE AMOUNT OF COFFEE PRODUCTION, VALUE EXCHANGE AND INFLATION ON COFFEE EXPORTS INDONESIA 2016—2020 - Rizky Amelia, Dian; Ludfi Arifin, Antoni; Hermawan, Eric (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
THE INFLUENCE OF THE AMOUNT OF COFFEE PRODUCTION, VALUE EXCHANGE AND INFLATION ON COFFEE EXPORTS INDONESIA 2016—2020